A Goal Programming Model with Satisfaction Functions for Portfolio Selection in Saudi Stock Market (The International Journal for Scientific Research, 2023)
This paper considers a goal programming model with satisfaction functions for portfolio selection problem taking into account conflicting objectives such us capital budget, return and risk in an imprecise investment environment. The aim of this paper is to formulate a multi-objective portfolio selection approach involving fuzzy parameters and incorporating explicitly the investor’s preferences through the concept of satisfaction functions. The proposed model is applied to data obtained from Saudi stock exchange. The empirical results show that the investor is well implied in the optimization and resolution process of the portfolio selection problem.
Keywords: portfolio selection; goal programming with satisfaction functions; investor’s preferences; capital budget; returns; cardinality; risk